Artificial insemination in white leghorn hens and its effects upon egg production, health and fertility - Resende, Osvaldo de Almeida; Monteiro, Joanna Maria Lafayette; Gomes, Walter Vígio; Dias, Paulo Genaro de Oliveira; Meneguelli, Carlos Alberto (Pesquisa Agropecuaria Brasileira, 2014)
The influence of artificial insemination on hen health and egg production and fertility was studied in 156 ten-month-old white Leghorn hens maintained in wire cages. Treatments compared were: Group A - biweekly inseminations; Group B - weekly inseminations; Group C – non-inseminated control. Each hen in groups A and B was inseminated with fresh, undiluted semen at a rate of 0.05 ml per insemination. Each treatment was composed of 26 replications (a replication being a cage of two hens) distributed in a completely randomized design. Mean egg production per cage per two week interval was: Group A - 19.35 (69.10%); Group B - 20.10 (70.17%); Group C - 18.96 (67.71%). The difference between Groups B and C was significant (P<0.05). No significant differences in mortality or incidence of cloacal infection were observed. There was a highly significant difference (P<0.01) in egg fertility between Group A (95.8%) and Group B (92.1%). These results indicate that artificial insemination does not have a detrimental effect on egg production or health of the hen.